(untitled) - Hyde, Charles K. (Princeton, N.J., 1977)
This book describes technological change in an industry that played a central role in the Indsutrial Revolution. While earlier scholars have examined isolated aspects of ironmaking in the eighteenth- and nineteenth-century Britain, Charles Hyde surveys all aspects of its development. Costs, prices, profits, shrewd leaders, competition, new inventions, and productivity all figure in this story of a key industry during the major period of its evolution.
Keywords: Công nghệ,Technology; Lịch sử,History; Nước Anh,Great Britain